Are the 1990 American College of Rheumatology vasculitis classification criteria still valid?. (31st March 2017) - Seeliger, Benjamin; Sznajd, Jan; Robson, Joanna C; Judge, Andrew; Craven, Anthea; Grayson, Peter C.; Suppiah, Ravi S.; Watts, Richard A.; Merkel, Peter A.; Luqmani, Raashid A.
Abstract: Objectives. Advances in diagnostic techniques have led to better distinction between types of vasculitis, potentially affecting the utility of the 1990 ACR classification criteria for vasculitis. This study tested the performance of these criteria in a contemporary vasculitis cohort. Methods. The Diagnosis and Classification in Vasculitis Study provided detailed clinical, serological, pathological and radiological data from patients with primary systemic vasculitis and clinical context-specific comparator conditions. Fulfilment of six ACR criteria sets and their diagnostic performance was evaluated in patients with a given type of vasculitis and its comparator conditions. Results. Data from 1095 patients with primary systemic vasculitis and 415 with comparator conditions were available. For classification, sensitivities and specificities for ACR classification criteria were, respectively, 81.1% and 94.9% for GCA; 73.6% and 98.3% for Takayasu's arteritis; 65.6% and 88.7% for granulomatosis with polyangiitis; 57.0% and 99.8% for eosinophilic granulomatosis with polyangiitis; 40.6% and 87.8% for polyarteritis nodosa; 28.9% and 88.5% for microscopic polyangiitis; and 72.7% and 96.3% for IgA-vasculitis. Overall sensitivity was 67.1%. Of cases identified by their respective criteria, 16.9% also met criteria for other vasculitides. Diagnostic specificity ranged from 64.2 to 98.9%; overall, 113/415 comparators (27.2%) fulfilled at least one of the ACR classification criteria sets. Conclusion. Since publication of the ACR criteria for vasculitis, the sensitivity for each type of vasculitis, except GCA, has diminished, although the specificities have remained high, highlighting the need for updated classification criteria.